Effects of different exercise types and cycles on pain and quality of life in breast cancer patients: A systematic review and network meta-analysis. - Jin Dong; Desheng Wang; Shuai Zhong (PLoS ONE)
Purpose To determine the effect of different combinations of different exercise modalities with different training cycles on the improvement of quality of life and pain symptoms in breast cancer patients. Methods The databases PubMed, Web of Science, Embase, and Scopus were searched through a computer network with a search deadline of 23 August 2023. Two researchers independently screened the literature, extracted data and performed methodological quality assessment of the included literature, and then performed the corresponding statistical analyses and graphing using stata17.0. Results Thirty-six randomized control trial (RCT) studies involving 3003 participants and seven exercise modalities were included. Most of the exercise modalities improved patients' quality of life compared to usual care, with long-term aerobic combined with resistance exercise [SMD = 0.83,95% CI = 0.34,1.33,p = 0.001] and YOGA [SMD = 0.61,95% CI = 0.06,1.16,p = 0.029] treatments having a significant effect. For pain and fatigue-related outcome indicators, the treatment effect was not significant for all exercise modalities included in the analysis compared to the control group, but tended to be beneficial for patients. Conclusion Long-term aerobic combined with resistance exercise was the most effective in improving quality of life and fatigue status in breast cancer patients, and aerobic exercise was more effective in improving pain symptoms in breast cancer patients.